Choosing important health outcomes for comparative effectiveness research: An updated systematic review and involvement of low and middle income countries - Davis, K; Gorst, S; Harman, N; Smith, V; Gargon, E; Altman, D; Blazeby, J; Clarke, M; Tunis, S; Williamson, P (Public Library of Science, 2018)
Core outcome sets (COS) comprise a minimum set of outcomes that should be measured and reported in all trials for a specific health condition. The COMET (Core Outcome Measures in Effectiveness Trials) Initiative maintains an up to date, publicly accessible online database of published and ongoing COS. An annual systematic review update is an important part of this process.This review employed the same, multifaceted approach that was used in the original review and the previous two updates. This approach has identified studies that sought to determine which outcomes/domains to measure in clinical trials of a specific condition. This update includes an analysis of the inclusion of participants from low and middle income countries (LMICs) as identified by the OECD, in these COS.Eighteen publications, relating to 15 new studies describing the development of 15 COS, were eligible for inclusion in the review. Results show an increase in the use of mixed methods, including Delphi surveys. Clinical experts remain the most common stakeholder group involved. Overall, only 16% of the 259 COS studies published up to the end of 2016 have included participants from LMICs.This review highlights opportunities for greater public participation in COS development and the involvement of stakeholders from a wider range of geographical settings, in particular LMICs.